TINJAUAN YURIDIS UU NO.16 TAHUN 2019 MENURUT ASAS MONOGAMI DAN HUBUNGAN HUKUM DALAM PERKAWINAN - Mieke Angraeni Dewi (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2020)
Marriage is a bond that gives birth to the family as one of the elements in social and state life, which is governed by the rule of law in written law (state law) and unwritten law (customary law). According to Law No. 16 of 2019 marriage and the aim is as follows: "Inner and outer bonds between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the Godhead of the One". Law Number 19 Year 2019 contains very broad contents, namely regulating marital problems, divorce, child status, rights and obligations between parents and children, and also regulating guardianship issues and regulating issues of proving the origin of children. Law Number 16 Year 2019 adheres to the principle that the prospective husband and prospective wife must cook their souls and bodies to be able to carry out the marriage, with the intention that in order to be able to realize the purpose of marriage properly without ending in divorce and to get good and healthy offspring. Therefore, in Article 7 paragraph (1) of Law Number 16 Year 2019, the age limit for marriage for men and women is 19 years and 19 years for women.